Study on thermochemical regeneration of exhausted activated carbon (EAC) and reusing it to regenerate exhausted triethylene glycol (ETEG) - Khochni abdelkader; BRAHIMI Djamila (Université Amar Thelidji- Laghouat-FACULTE : TECHNOLOGIE DEPARTEMENT : GÉNIE DES PROCÉDÉS, 2025)
The regeneration of spent activated carbon (EAC), used in the adsorption of volatile organic compounds (VOCs) within triethylene glycol (TEG) dehydration units, is considered a more sustainable and economical alternative to disposal. This study aims to evaluate the thermo- chemical regeneration method by determining the optimal key parameters, such as the mass ratio (mKOH/mEAC), temperature, and regeneration time. The regenerated activated carbon (RAC) was also tested for its effectiveness in purifying spent glycol, using low- concentration alkaline chemical washing followed by thermal treatment. The best factors, including the mass ratio (mETEG/mRAC) and regeneration time, were identified. Experimental results showed that this combined approach significantly enhances the iodine number of the regenerated carbon and restores the physicochemical properties of TEG, making it a practical and economical option for reuse in the gas and petrochemical industries.
OPTION : Petrochemical engineering